تطور تطبيقات نظرية الظروف الطارئة في النظام والقضاء الإداريين السعوديين - الضويان، فهد بن إبراهيم (جامعة الملك سعود - كلية الحقوق والعلوم السياسية, 2014)
تناولت هذه الدراسة نظرية الظروف الطارئة التي ابتدعها القضاء الإداري (مجلس الدولة الفرنسي)، خلال الحرب العالمية الأولى نتيجة تغير الظروف التي أبرمت في ظلها العقود الإدارية، مما تسبب في إرهاق مالي للطرف المتعاقد مع الإدارة، وحتم وقوف الإدارة مع هذا المتعاقد المتعثر ومشاركته بالخسائر من أجل تحقيق مقتضيات العدالة وضمان حسن سير المرافق العامة، وكان هذا التوجه مناقضا لما استقرت عليه العقود المدنية في فرنسا (العقد شريعة المتعاقدين). أما النظام القانوني السعودي المرتكز على الشريعة الإسلامية فلم يجد صعوبات في تطبيق هذه النظرية، لما يتحقق من إعمالها من عدل وإعادة التوازن المالي وإنصاف المتعاقدين مع الإدارة. من أجل ذلك طور المنظم السعودي والقضاء الإداري السعودي (ديوان المظالم) خلال عهده الأول (قبل 1402 هـ-1982م) والحالي (بعد 1402 هـ-1982م)، تطبيق نظرية الظروف الطارئة وفق ما استقر عليه الفقه والقضاء الإداريان المقارنان.
This study of discuss the study of theory emergency circumstances which removed the administrative judiciary (French Council of State), during the First World War as a result of changed circumstances which concluded in which administrative contracts, causing fatigue Financial to Contracting Party with the administration, and inevitably parking management with this contractor struggling and share losses of in order to achieve the requirements of justice and ensure the proper functioning of public utilities, and this trend was contrary to the settled civil contracts in France (pacta sunt servanda). The Saudi legal system based on Islamic law which have not found any difficulties in applying this theory, to verify the realization of justice and restore fiscal balance and fairness contractors with management), For that developed Saudi legislator and Administrative Justice (Diwan Al Madhalim) during his first (before 1982) and the current (after 1982), application the theory emergency circumstances as settled jurisprudence and comparative administrative court and contemporary.
Keywords: المنازعات الإدارية -- المملكة العربية السعودية -- القضاء الإداري -- الشريعة الإسلامية -- المرافق العامة -- النظم الإدارية -- القرارات الإدارية -- نظرية الظروف الطارئة -- الأحكام الإدارية